STUDY OF THE CONDITIONS OF ALKALIZATION AND AMINOLIZATION OF SECONDARY POLYCARBONATE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article presents the process and results of the alkolysis and aminolysis of secondary polycarbonate. The main focus is on the decomposition of secondary polycarbonate (IPC) to the monomer bisphenol A (BPA), and the effect of aminolysis and alcoholysis on the yield of bisphenol A (BPA) is studied. The main physicochemical parameters of the resulting product are presented.